Convexity for Interval Valued Neutrosophic Setsand its Application in Decision Making - Suthi Keerthana Kumar; Vigneshwaran Mandarasalam; Saied Jafari; Rose Venish Ayyakanupillai Gnanaudhayam; Vidyarani Lakshmanadas (Neutrosophic Sets and Systems)
The notion ‘Convexity’ is applied in various areas of mathematics particularly in optimization techniques. It is known that this concept is applied in fuzzy sets, which is studied by many authors. This article deals with convexity utilized for neutrosophic and interval valued neutrosophic sets which is a generalization of intuitionistic fuzzy sets. Also some interesting preservation properties of convexity under intersection operators in interval valued neutrosophic sets are discussed. Adding to the discussion, preservation property of digital convexity under intersection using deformation and other techniques are touched upon. Eventually the application of convexity to decision making are illustrated using examples.